Health researchers' experiences, perceptions and barriers related to sharing study results with participants - Christopher R. Long; Rachel S. Purvis; Elizabeth Flood-Grady; Kim S. Kimminau; Robert L. Rhyne; Mark R. Burge; M. Kathryn Stewart; Amy J. Jenkins; Laura P. James; Pearl A. McElfish (BMC, 2019)
Abstract Background Although research participants are generally interested in receiving results from studies in which they participate, health researchers rarely communicate study findings to participants. The present study was designed to provide opportunity for a broad group of health researchers to describe their experiences and concerns related to sharing results (i.e. aggregate study findings) with research participants. Methods We used a mixed-methods concurrent triangulation design, relying on an online survey to capture health researchers' experiences, perceptions and barriers related to sharing study results with participants. Respondents were health researchers who conduct research that includes the consent of human subjects and hold a current appointment at an accredited academic medical institution within the United States. For quantitative data, the analytic strategy focused on item-level descriptive analyses. For the qualitative data, analyses focused on a priori themes and emergent subthemes. Results Respondents were 414 researchers from 44 academic medical institutions; 64.5% reported that results should always be shared with participants, yet 60.8% of respondents could identify studies in which they had a leadership role where results were not shared. Emergent subthemes from researchers' reasons why results should be shared included participant ownership of findings and benefits of results sharing to science. Reasons for not sharing included concerns related to participants' health literacy and participants' lack of desire for results. Across all respondents who described barriers to results sharing, the majority described logistical barriers. Conclusions Study findings contribute to the literature by documenting researchers' perspectives and experiences about sharing results with research participants, which can inform efforts to improve results sharing. Most respondents indicated that health research results should always be shared with participants, although the extent to which many respondents described barriers to results sharing as well as reported reasons not to share results suggests difficulties with a one-size-fits-all approach to improving results sharing.